System design and circuit implementation of a solar powered car - Khatun, Karima; Chowdhury, Radita; Kabir, Mad. Sazzad Ul; Sarker, Shreya (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.